Effect of caffeinated coffee on running speed, respiratory factors, blood lactate and perceived exertion during 1500-m treadmill running. Issue 2 (June 1992) - Wiles, J D; Bird, S R; Hopkins, J; Riley, M
Abstract : Using a motorized treadmill the study investigated the effects of the ingestion of 3 g of caffeinated coffee on: the time taken to run 1500 m; the selected speed with which athletes completed a 1-min 'finishing burst' at the end of a high-intensity run; and respiratory factors, perceived exertion and blood lactate levels during a high intensity 1500-m run. In all testing protocols decaffeinated coffee (3 g) was used as a placebo and a double-blind experimental design was used throughout. The participants in the study were middle distance athletes of club, county and national standard. The results showed that ingestion of caffeinated coffee: decreases the time taken to run 1500 m (P less than 0.005); increases the speed of the 'finishing burst' (P less than 0.005); and increases VO2 during the high-intensity 1500-m run (P less than 0.025). The study concluded that under these laboratory conditions, the ingestion of caffeinated coffee could enhance the performance of sustained high-intensity exercise.